Wireless intelligent indoor LED lighting project through Wi-Fi and 3G network - Wu, Jin (2015)
In this report, a LED lighting control system based on the Wi-Fi network is proposed. The project includes Several LEDs, a lighting control APP for both iOS and android platform and a Wi-Fi enabled Soc module for PWM and remote control. The hardware and software design &implementation will be elaborate in detail in chapter 3. The results show that the Soc used which is esp8266, is an ideal choice for IOT implementation. Smart phone, as a common device used in our daily life is an ideal selection for household appliances control.